A novel concept for enhancement of the buckling capacity of thin plates via geometric modification - Chennapragada, Maharaghni; Nazam, Malik Sheraz (My University, 2021)
The extensive use of thin-walled structures in various field owing to their know ad vantages motivates the further research to mitigate their failure due to buckling. Thin-walled members are dominantly susceptible to failure due to the buckling, so, a great effort has been devoted in the past decades to postpone the buckling using different stiffening approaches. However, almost all these techniques result in ad ditional weight which reduces their lightweight performance. So, this study deals with assessing an innovative idea of increasing the buckling performance by the in troduction of multiple stiffening shapes of thin-walled panel without increasing the mass of the plate.Flat plates are strengthened based on the innovative concept with various geometrical configuration of augmented sub-surface areas and subjected to varying type of in-plane loads. A comprehensive linear buckling parametric study is conducted over a wide range of varying dimensions, loading, and stiffening shapes to investigate their effect on critical buckling capacity and identify the optimal geometry. Thin plates with thick ness ranging from 0.05% to 1% of their width are analysed for multiple stiffening shapes and pattern. Stiffening unit cell shapes include circular, square, triangle and capsule. The study is carried out by developing FE parametric models in a programming language known as Python relying on the use of finite element (FE) software ABAQUS-CAE, to run a large number of simulations and gather results in an efficient manner. Sensitivity analyses are conducted over multiple geometrical parameters in relation to critical buckling load, leading to recommendation of most optimal patterns according to the implemented shape stiffening concept. FE method of analysis is validated through comparison with available analytical so lution in the literature for flat buckling under uni-axial, bi-axial and shear loading. Over the specified thickness range, an extensive parametric study is conducted with circular-unit-cell shape stiffeners.About Two thousand and sixty models for each the three aspect ratios and three load case generates a total of more than eighteen thou sand five hundred cases. Due to the time-consuming nature of the computations the parallel processing cluster computing facility at Chalmers is utilised to execute, gather and export results. Hence the obtained results constituted a large range of comparable parameters and their dependency on improvement of buckling capacity is assessed. The results highlight the importance of stiffener density and dimensions. This stiffening is observed to be most beneficial for thinner plates and as the thick ness increased, the % improvement decreased. The study of the results also reflect upon the importance of careful selection of the most optimized pattern for a design.situation. In order to examine the unit-cell shape’s potential for enhancement of the buckling load capacity, in addition of a large number of modeling and analyses of the circular stiffening shape, other geometric shapes are examined, including square, triangular and capsule shaped stiffeners. The square space with most surface area offered the best improvement compared to others. Results from non-linear analysis reflect that geometric and material non linearity is affecting buckling strength of flat plate and stiffened plate in similar proportion. Non-linear analysis also indicate that stiffening shapes are leading to more uniform distribution of stress as compared to flat plate. For varying plate thickness, recommended stiffening patterns yield 114% - 1143% of increase in buckling capacity, conclusively establishing enhanced buckling capac ity by introducing stiffening shapes. The varying level of disturbance to the first buckling mode depending on the shape and size of stiffeners leads to an increase in buckling capacity. Study results lead to a new technique in the research area of strengthening thin-walled structures without increasing the consumed constituent materials or adding the structures total weight.
Keywords: Shape Stiffeners, Linear Buckling, ABAQUS, PYTHON, Thin Plates; Post Buckling